Price, Taste, and Convenience: A Comparative Study on School-Based and Commercial Pastil Vendors - Olay Jr., Salahuddin A.; Noble, Adrian Eric A.; Pelmin, Monsour A. (International Journal of Research in Interdisciplinary Studies, 2025)
Pastil is a staple and popular food at Mindanao State University-General Santos City (MSU-GSC), especially among students. It specifically compares how Price, Taste, and Convenience influence their decision when choosing between vendors located inside the school and commercial vendors located outside the campus. The researchers used a descriptive-comparative method and gathered quantitative data through surveys. These surveys were given to students both in-person on paper and online using Google Forms, based on a convenience sampling technique. The findings were analyzed using descriptive statistics, such as averages and percentages. The results showed that convenience was the most dominant factor for students. They overwhelmingly choose school-based vendors because they are close to classrooms and dorms, which is essential for busy schedules or short breaks. Students even said they are not likely to leave campus just to buy pastil, even if they have extra time, making outside vendors mostly a "backup option". The taste was surprisingly not a major deciding factor; the results were balanced, showing students had mixed preferences between the two types. For price, students were found to be value-driven, looking for good "value for money" rather than just the lowest cost. The study concluded that students ultimately balance all three factors Price, Taste, and Convenience to find the best combination for their specific needs at that moment.